The Dynamics of Contract Marriage in the Puncak Bogor Indonesia: A Review of Muslim Social Norms, Tourism Economics, and Gender Vulnerability - Nunung Nurwati; Muhamad Fedriansyah; Willya Achmad (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2026)
The practice of contract marriage in West Java has developed as a social phenomenon that is not merely associated with violations of legal norms or marital morality, but also reflects gendered power relations shaped by tourism-based economic structures and local social inequalities. This article aims to analyze the practice of contract marriage through a gender sociology perspective by emphasizing the interaction between local patriarchy, the informal tourism economy, and women’s agency negotiation under structural constraints. Furthermore, this practice persists through a dual framework of cultural-religious legitimacy, where certain religious interpretations are manipulated to justify temporary unions while masking underlying socio-economic exploitation. This research employs a qualitative case study approach conducted in the Bogor–Cianjur–Puncak tourism area through in-depth interviews with individuals involved in contract marriage practices and relevant local actors, field observations, and document analysis. A total of 14 informants were purposively selected based on their direct involvement or knowledge of the practice. The findings indicate that women’s participation cannot be fully understood as an autonomous individual choice, but rather as a negotiated response within conditions of limited access to education, restricted formal employment opportunities, and family economic pressures. Contract marriage functions as both a survival economic strategy and a process of commodification of women’s bodies legitimized through local intermediary networks and the demands of transnational tourism markets. These findings affirm that contract marriage represents a manifestation of gender inequality reproduced within tourism economic structures. Therefore, gender-sensitive policy approaches are required through strengthened legal protection for women, local economic diversification, and community-based social interventions, including gender-sensitive religious counseling, to reduce the reproduction of structural vulnerability in tourism areas.